A Dick and Carey-Based English Learning Model: Integrating Culture Based Learning, Islamic Values, and HR Management - Enawar Enawar; Euis Yanah Mulyanah; Desri Arwen; Sholeh Hidayat; Luluk Asmawati; Ishak Ishak (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study addresses the gap in culturally contextualized English language instruction in higher education, where teaching often overlooks students’ sociocultural backgrounds. The research aimed to develop and evaluate an English learning model integrating Rampak Bedug—a traditional Banten performance rich in Islamic values—using the Dick and Carey instructional design model combined with the Culture-Based Learning (CBL) approach. The model was implemented with second-semester students of the English Education Department at Universitas Muhammadiyah Tangerang during the 2024–2025 academic year. A descriptive qualitative method was used, with data collected through observation, interviews, project documentation, and reflective journals. Instructional strategies incorporated visual and auditory media—such as videos, traditional costumes, and musical instruments—alongside group discussions, project-based writing, and reflective activities. Findings indicated improvements in students’ descriptive writing skills, digital literacy, and cultural awareness. The integration of Rampak Bedug fostered engagement by embedding values such as harmony, discipline, sincerity, and cooperation. Formative evaluations led to revisions in visual aids and linguistic scaffolding. Summative evaluations highlighted enhanced student collaboration, creativity, and reflective practice. In conclusion, this culturally grounded, multimodal instructional model supports communicative language learning while promoting professional development skills aligned with human resource management principles, such as teamwork and instructional planning. The model demonstrates strong potential for replication across educational levels and cultural settings in Indonesia, offering a transformative, socially relevant approach to English language pedagogy.